Nonlinear summation of contractions in cat muscles. I. Early depression (The Rockefeller University Press, 1981)
Nerves to fast- and slow-twitch cat muscles were stimulated with various numbers of supramaximal pulses under isometric conditions. By subtracting the force produced by j - 1 pulses from that produced by j pulses, the contribution of the j th pulse could be compared with the response to one pulse (twitch response). A less-than-linear summation (depression) was observed during the rising phase of the twitch. This depression became increasingly prominent and longer in duration with repetitive stimulation. A more-than-linear summation (facilitation) was observed during the falling phase of the twitch, which became increasingly delayed and smaller in amplitude with repetitive stimulation. The early depression could be abolished for the first few pulses by Dantrolene [1-(5-p-nitrophenyl) furfurilidene amino hydantoin sodium hydrate], which reduced Ca++ release from the sarcoplasmic reticulum. The depression was less prominent at short muscle lengths or with stimulation of single motor units. A first-order, saturable reaction such as Ca++ binding to troponin or actin binding to myosin can quantitatively account for the early depression.